An IOT Based Vehicle Accident Detection and Speed Control - et. al., K.Pradeep Mohan Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
An embedded system has been designed to make the journey of the passengers inside a vehicle safe and secure with using the Internet of things. IOT is almost an adjustable technology that is capable of providing relevant information about its own operation. It provides the necessary accident information to the vehicle. In today’s world safety and security plays an important role, Vehicles are important in our fast-paced society, hence we move towards intelligent security systems while travelling. There are too many warning systems incorporated in the vehicles to alert drivers about various factors like eye blink, driver’s head movement, detecting alcohol consumption. This wireless system monitors the outside environment of the vehicle. This model consists of a node MCU, a motor, an ultrasonic sensor, a PIC controller and IOT. A PIC microcontroller chip is a Peripheral Interface Controller. Distance of vehicles are determined by using an ultrasonic sensor, and the distance is calculated over a simple period of time that detects distance of obstacles outside the vehicle through ultrasonic sensor that continuously sends signals, If any obstacles spotted then the motor turns slow that indicates the speed of a vehicle. All these distances are stored on to the server using the node MCU module. This accident information can be seen through website or application that will enhance the security of the system.